2010
DOI: 10.1186/1465-9921-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of apoptosis mediators' p53 and bcl2 in lung tissue of COPD patients

Abstract: Abnormal apoptotic events in chronic obstructive pulmonary disease (COPD) subvert cellular homeostasis and may play a primary role in its pathogenesis. However, studies in human subjects are limited.p53 and bcl2 protein expression was measured by western blot on lung tissue specimens from 43 subjects (23 COPD smokers and 20 non-COPD smokers), using beta-actin as internal control. Additionally, p53 and bcl2 expression patterns were evaluated by immunohistochemistry in formalin-fixed, paraffin-embedded lung tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 35 publications
(62 reference statements)
3
47
0
Order By: Relevance
“…As shown in Figures 7B and 7C, both were elevated in COPD tissue relative to control and expression increased with worsening severity. This is consistent with previously published data showing increased p53 protein levels in lungs of smokers with COPD compared with lungs of smokers without COPD (23,50).…”
Section: Dna Damage Is Increased In Copdsupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Figures 7B and 7C, both were elevated in COPD tissue relative to control and expression increased with worsening severity. This is consistent with previously published data showing increased p53 protein levels in lungs of smokers with COPD compared with lungs of smokers without COPD (23,50).…”
Section: Dna Damage Is Increased In Copdsupporting
confidence: 93%
“…For instance, p53 is increased in type II pneumocytes of smokers with COPD relative to smokers without COPD (23), and patients with COPD have shortened telomeres in peripheral blood compared with control subjects, independent of smoking history (24). This may be caused by dysregulated antioxidant defense mechanisms (24) or repeated cycles of lymphocyte activation and proliferation (25), but a third possibility is that these individuals have impaired ability to repair double-strand DNA breaks resulting in premature telomere shortening (26).…”
mentioning
confidence: 99%
“…Given that hMSC have been shown to mediate anti-inflammatory effects8, reduce oxidative stress, reduce fibrosis and enhance repair30 it seems logical that hMSC might represent a suitable and efficacious therapy for COPD. Key pathological mechanisms of epithelial damage and wound formation occur in COPD, eventually leading to development of emphysema3132. This study has shown that hMSC possess potent cytoprotective and reparative abilities that may limit these activities.…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that the classic anti-apoptotic protein, Bcl-2, might present protective potential for emphysema. 8,[11][12][13] whereas the pro-apoptotic protein, Bax, might contribute to emphysema progress. [14][15][16] Some studies described methylation, an important epigenetic event, participated in regulation of Bcl-2 and apoptosis.…”
Section: Introductionmentioning
confidence: 99%